Strategic plan for DILG-XI Employees Multi-Purpose Cooperative - Enad, Erwin M. (School of Management, University of the Philippines Mindanao, 2007)
The formation of any cooperative has always been imbued with public interest. Its peculiarity as non.typical business entity arises from its being an effective instrument in redistributing income and wealth. It bears to emphasize that it is mutuality of cooperation among its members for that purpose that separates it from other on-going concern. This paper provides logical discussion and presentation on the strategic direction of the Department of the Interior and Local Government Employees Multi-Purpose Cooperative (DEMPC) for the year 2007-2011. This study is anchored on the framework of Fred David which utilizes three (3) phases, viz: (1) strategy formulation; (2) strategy implementation; and (3) strategy evaluation. This study will reveal the interdependence of each phase to effectuate the ultimate goal of putting into reality the vision for which the DEMPC was formed. Several tools of analysis were used in all phases of this study inasmuch as the nature of the DEMPC demands that its social relevance should not be taken out of the context. This study will present lucidly several factors affecting the operation of DEMPC as employee cooperative and social enterprise and how cultural nuances play a very significant role in the decline and survival of the cooperative. An evaluation of external forces affecting DEMPC readily provides the following opportunities and challenges, viz: (a) favorable economic fundamentals encourages DEMPC to engage in social economic enterprise; (b) strong governmental support on cooperative movement as a means of achieving social ends; (c) Issuance of E.O. 366 by President Gloria Macapagal-Arroyo which declares redundant some positions of DILG and thus, eventually affects the membership of DEMPC; and (d) best practices from existing cooperatives and federations which may be replicated by DEMPC to take advantage of its being ?multi-purpose cooperative, non-agricultural category? rather then confine on credit services. An evaluation of internal forces affecting DEMPC reveals the following strengths and weaknesses: (a) profitability and solvency indicators for DEMPC; (b) Captured market due to exclusivity of membership of DEMPC to DILG Personnel; (c) high delinquency rate de to lax credit policy; (d) ?personalistic? dealings in cooperative transactions since loan policies and operational guidelines were not strictly complied with; and (e) demand for institutional strengthening due to inability of members and officers to fully grasp the reason of existence of DEMPC. Accordingly, matching of the strengths and weaknesses with the opportunities and challenges generated six strategies which were fused into three, to wit: (a) engage in economic enterprise; (b) leadership and membership development; (c) strict policy adherence; and (e) notarization of documents and pursuit of legal action against delinquent borrowers. In its proper sequence, plan implementation commences with institutional strengthening, pursuit of legal action and venture in economic enterprise. Goals action plan were crafted for the specific implementation of the four strategic plans. Anent the monitoring and evaluation phase, this paper utilizes the Balanced Scorecard System of Robert Kaplan and David Norton taking into consideration the four perspectives as Key Results Area (KRAs). Corresponding performance indicators were prepared to gauge the attainment of goals.